Urban parks as creative centers: promoting art and imagination: Innovation, Art and Technology: New Frontiers in Urban Spaces - Hernández Joya, Lady Paola; Tavera Castillo, Nancy; Martínez Cerveleon, Adriana (Street Art & Urban Creativity, 2025)
The proposal "Urban Parks as Creative Centers: Fostering Art and Imagination" aims to transform Bucaramanga’s parks into creative learning spaces through the "Creative Train" program. This project offers free workshops for children, covering art, recycled crafts, music, theater, creative science, and technology such as 3D printing and simulators with augmented reality, encouraging their creativity. The workshops will take place in themed train carriages, providing an educational and fun environment. All workshops will be free to ensure inclusivity for all families. Additionally, partnerships with local educators, artists, and professionals will be established to enrich the activities. This project aims to revitalize the parks as cultural meeting spaces, improving the quality of life for children and strengthening Bucaramanga’s social fabric, turning the parks into vibrant, lively places.